MANAJEMEN SEKOLAH RAMAH ANAK DI SEKOLAH ALAM BIREUEN (SABIR) - Zulfridiana, Zulfridiana; Yanti, Hera; Rizki, Sari (Hijri, 2024)
This study aims to analyze the management of Child-Friendly Schools (Sekolah Ramah Anak/SRA) at Sekolah Alam Bireuen (SABIR), focusing on three main aspects: planning, the availability of educators and education personnel, and the supporting facilities for implementing SRA. The background of this research is the urgency to fulfill children's rights in educational settings, as mandated by Law No. 35 of 2014 and the Convention on the Rights of the Child (CRC). This research uses a qualitative approach with data collected through interviews, observations, and documentation. The results show that SRA planning at SABIR is carried out in a participatory and contextual manner, involving students through class forums and the student council (OSIS), as well as parents through parenting sessions and community meetings. However, SABIR has not yet received a formal decree (SK) from the local government declaring it an official Child-Friendly School. In terms of educators, two teachers have received independent training related to child rights via the Merdeka Mengajar platform, although no official SRA certification has been granted. Regarding facilities, the school has provided several child-friendly features such as separate toilets, evacuation routes, and open-air classrooms that utilize the natural environment. Nonetheless, limitations still exist, such as the absence of key SRA symbols and a lack of inclusive infrastructure. This study recommends stronger formal support from the government, more structured training for teachers on SRA principles, and further development of facilities rooted in local and ecological values. The findings contribute theoretically to child-friendly school management studies and offer practical insights for schools and policymakers in building inclusive, safe, and joyful learning environments for children